An evaluation of interactive projections as digital enrichment for orangutans. Issue 2 (27th January 2021) - Carter, Marcus; Sherwen, Sally; Webber, Sarah
Abstract: Digital technologies are increasingly being incorporated into the provision of enrichment for captive primates, ranging from the ad‐hoc use of iPads to specifically designed hardware installed in the design of new exhibits. In this article, we present a digital enrichment system that utilizes a novel approach with interactive projections, installed in the orangutan exhibit at Melbourne Zoo. While previous research into orangutan enrichment has involved reinforcement using food rewards, this study is the first investigation of digital enrichment for orangutans that does not involve food rewards. Rather, the interactive projections were designed to provide intrinsically rewarding environmental enrichment, instead of a cheaper or more variable way of delivering food. Our observations of orangutans' use of the system supports the approach of using interactive projections, finding that it is more responsive than capacitance or resistive based touch‐screen technologies to the variety of ways that orangutans "touch": with whole hands, feet, faces, and with objects. We also present the results from a preliminary study into the effect of this enrichment into orangutan behavior which found presence or use of the device did not affect time spent engaged in the majority of behaviors of the individuals studied. Abstract : Interactive projections provide a novel form of digital enrichment for Orangutans, not requiring the motivation of food rewards. Research Highlights: Interactive projections provide a novel form of digital enrichment for Orangutans, not requiring the motivation of food rewards